1991
DOI: 10.1073/pnas.88.6.2127
|View full text |Cite
|
Sign up to set email alerts
|

Diacylglycerols induce both ion pumping in patch-clamped guard-cell protoplasts and opening of intact stomata.

Abstract: Stomatal guard cells in leaves regulate the apertures of microscopic pores through which photosynthetic gas exchange and water vapor loss occur. Environmental signals, including light, high humidity, and low CO2 concentrations, open stomata by increasing the volume of guard cells. Activation of a plasma membrane HI pump initiates K+ and Cl-influx, accompanied by malate synthesis, resulting in osmotic water flow into the guard cells, a bowing apart of the guard-cell pair, and consequent stomatal opening. Physio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0

Year Published

1991
1991
2010
2010

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(43 citation statements)
references
References 31 publications
2
41
0
Order By: Relevance
“…Among the 74 proteins enriched in GC described in the previous section, 15 are represented on the microarray, and nine transcripts were identified as enriched in GC (supplemental Table 2). These results confirm the general observation that mRNA levels are not always consistent with protein levels because of post-transcriptional, translational, or post-translational regulations (32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44). They also highlight the importance of proteomics analysis.…”
Section: Comparative Analysis Of Transcriptome Data and Proteome Data-supporting
confidence: 76%
See 1 more Smart Citation
“…Among the 74 proteins enriched in GC described in the previous section, 15 are represented on the microarray, and nine transcripts were identified as enriched in GC (supplemental Table 2). These results confirm the general observation that mRNA levels are not always consistent with protein levels because of post-transcriptional, translational, or post-translational regulations (32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44). They also highlight the importance of proteomics analysis.…”
Section: Comparative Analysis Of Transcriptome Data and Proteome Data-supporting
confidence: 76%
“…It is important to note that we identified proteins known to specifically function in GC (most of low abundance) but were not able to obtain reproducible quantitative information. These proteins include G protein (30,31), Rac GTPase (32,33), phospholipase D 1 (34), protein kinase C (35,36), open stomata protein kinase (6), Atrboh (40), and profilin (41).…”
Section: Functional Specialization Of Proteins In Guard Cells Andmentioning
confidence: 99%
“…DAG may function directly as a mediator and/or phosphorylated by DGK to PA. DAG in itself is a potent messenger in animal cells, but its role in signaling in plants is unknown. A previous study using Vicia faba and synthetic DAG indicated that DAG promoted stomatal opening by activating an ion pump in the guard cell plasma membrane and inhibits stomatal closure by possibly inhibiting K + efflux (Lee and Assmann, 1991). This study shows that under well-watered control conditions, npc4-1 plants had lower stomatal conductance and transpiration rates than the wild type, whereas NPC4-OE tended to have higher stomatal conductance than the wild type.…”
Section: Npc4 and Dag Promote Stomatal Opening Under Well-watered Conmentioning
confidence: 64%
“…MLCK (8,19). More recently, Lee and Assmann (18) showed that 1,2-diacylglycerol, a physiological activator of protein kinase C in animal cells, stimulated both stomatal opening in the epidermis of C. communis and an ATP-dependent, voltageindependent outward current across the plasma membrane of Vicia guard cell protoplasts, suggesting the activation of an electrogenic ion pump via protein kinase C. Moreover, they indicated that H-7, a preferential inhibitor of protein kinase C, inhibited light-dependent stomatal opening in Commelina epidermis. Although these results appear to conflict with our present findings, it should be noted that our study centered only on the blue light-dependent responses, whereas the effect of 1,2-diacylglycerol was elicited in both light and darkness.…”
Section: Effects Of Cam Antagonists On Blue Light-dependent Proton Pumentioning
confidence: 99%